On absolute, perfect, and unconditional convergences of double series in Banach spaces - Kadets, M. I. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We prove that, in the case of double series, perfect and unconditional convergences coincide, while absolute and perfect convergences do not coincide even for numerical series.